PENGARUH METODE MENDONGENG (STORY TELLING) TERHADAP HASIL BELAJAR IPS KELAS IV SEKOLAH DASAR - Sahara, Annisa Elva; Supratno, Haris; Rochmania, Desty Dwi (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2020)
Adding insights about the results of the pretest-posttest as well as the influence of when or without using the storytelling method on social studies learning results in grade IV elementary schools is the purpose of this study. The research design used was a quasi-experimental design with a pretest-posttest design, non equivalent control group design. Where examining two groups, that is the experimental class and the control class in one class. Grade IV elementary school students, that is group A and group B are the population in this study. Sampling technique is a technique used in determining research samples. The test of student social studies learning results (cognitive) that has been tested for validity by experts is a research instrument. The test analysis used is the normality test and hypothesis testing. The results showed that there was a significant influence in the use of storytelling methods on social studies learning results. The results of the t-test show that learning without using the method of storytelling is in the control class with tcount (7,786)> ttable (2.131). The same from the t test on learning using the story telling method, is in the experimental class with tcount (10.647)> t table (2.131). This proves that there is a positive influence on the use of storytelling methods on social studies learning results in grade IV elementary schools. The use of the storytelling method can help teachers in providing creative learning, giving students freedom in conveying their ideas and creativity in understanding the material and being presented in learning that is not boring will make students interested in the learning that takes place so that the material can be conveyed well.